Career Perceptions in Fashion and Design Technology Programmes among TVET Students and Teachers in the Northern Region of Ghana - Saana, Alfredina; Abraham, Isaac; Asobayire, Joyce (Advances in Social Sciences Research Journal, 2025)
The goal of vocational education worldwide is to provide students with employable skills and better sharpen their career prospects. In Ghana however, several students have gone through Technical and Vocational Education and Training (TVET) programmes with little prospects to show. This study therefore sought to examine the perception of students and teachers on career prospects in the fashion and design technology programme of TVET in the Northern Region of Ghana. The study employed an institution-based cross-sectional study design. A stratified random sampling procedure was used to recruit 320 participants, who questionnaires were administered to. Data were analysed using Statistical Package for Social Sciences (SPSS). The findings showed that, the fashion and design programmes were not well structured by policymakers to equip students with employable skills. Respondents stated that there were low career prospects in fashion and design because teachers mostly taught theory rather than practical oriented. It was revealed that the fashion and design programmes provided specific job skills that made it difficult for career progress in an ever-changing environment. Respondents also identified fashion and design to be meant for academically weak students. In conclusion, the respondents perceived career prospects in the fashion and design programme to be limited and recommended that institutions should reconsider redesigning the programme to reflect current needs of employers.